IJCM_241A: Perception of the effectiveness of small group teaching and didactic classes among Health Science students - Darshan B B; Tolambiya Kshitiz; Siwach Prateek; Akshaya K M; Krishnan Rahul (Wolters Kluwer Medknow Publications, 2024)
Background: The global trend towards the teaching and learning process is becoming more dynamic and interactive compared to traditional didactic lectures. Medical schools are changing their teaching strategies to ensure that students are prepared for lifelong. Objectives: To determine the perception of the effectiveness of small group teaching and didactic classes among health science students. Methodology: This was a cross-sectional study conducted among 300 undergraduates of Kasturba Medical College, Mangalore, and undergraduates of Manipal College of Dental Sciences, Mangalore. Data was entered and analyzed using SPSS version 29.0. The results were expressed in the form of tables and graphs. Results: Among the BDS students most of them were in the Second year (53.3%) and Third year (28.3%). Around 17% of students preferred SGT as it was an interactive session, 17% preferred it as it helps the application of knowledge and 23% of students chose SGT as it provides them an opportunity to present, and as their confidence 28% favored SGT as it enhances thinking ability 15% selected SGT as was a mode self-learning. Conclusion: Most of the undergraduates supported SGT over DIDACTICS. SGTs were found to be the method that provides an opportunity to clear doubts. Under the type of SGTs, many students preferred problem-based learning type, followed by seminars and flip classes.